1994
DOI: 10.1136/hrt.72.4.321
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early mortality and morbidity after single and bilateral internal mammary artery grafting with the free right internal mammary artery.

Abstract: Objective-To compare differences in early mortality and morbidity in patients receiving a single internal mammary artery graft (SIMA) with those receiving bilateral internal mammary artery grafts (BIMA) with a free right internal mammary artery (RIMA). Design-Retrospective analysis of 150 patients undergoing BIMA grafting between [1989][1990][1991][1992]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Data from the UK’s Health Survey of England found that the prevalence of CVD was at least 30–40% higher in South Asians compared to Caucasians [11–13]. In the UK, it has been shown that second generation South Asians also have a higher risk for CVD [14]. Additionally, the SHARE study in Canada found the prevalence of CAD in South Asians to be more than twice that of Caucasians and Chinese [15].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the UK’s Health Survey of England found that the prevalence of CVD was at least 30–40% higher in South Asians compared to Caucasians [11–13]. In the UK, it has been shown that second generation South Asians also have a higher risk for CVD [14]. Additionally, the SHARE study in Canada found the prevalence of CAD in South Asians to be more than twice that of Caucasians and Chinese [15].…”
Section: Introductionmentioning
confidence: 99%
“…The success of myocardial revascularization mainly depends on long-term graft patency and the number of bypassed coronary arteries. Recently, it has been stated that the use of the bilateral internal mammary artery (BIMA) in coronary artery bypass grafting (CABG) operations has improved functional capacity, reduced the rate of reintervention, prolonged survival, and decreased the rate of reoperation without increasing morbidity and postoperative early mortality when compared to the use of the left internal mammary artery (LIMA) [Pick 1997;Tatoulis 1999;Lytle 1999;Endo 2001;Dewar 1995;Berreklouw 2001;He 1994;Ashraf 1994;Ioannidis 2001;Toker 2000]. Fiore and associates [1990] concluded that the right internal mammary artery (RIMA) to right coronary artery (RCA) anastomosis in BIMA-operated patients had good effects, reduced the long-term angina and myocardial infarction frequency, and decreased reintervention rate.…”
Section: Introductionmentioning
confidence: 99%
“…A second arterial conduit to a non‐LAD target has less potential to impact on overall survival than the single left internal thoracic artery to the LAD. Solid evidence suggests, in fact, that in coronary artery bypass surgery, patient survival is mainly determined by the status of the LAD and that grafts to non‐LAD vessels are more likely to affect other cardiac end points (myocardial infarction, angina recurrence, and need for revascularization), but not overall survival . The LAD also can provide collaterals to other coronaries (commonly the right coronary); a persistently patent internal thoracic artery graft to the LAD can therefore supply not only the anterior wall, but, through collaterals, viable myocardium in other territories.…”
Section: Discussionmentioning
confidence: 99%